Definition to Ethnotoponyms and research the ethnic history of the Uzbek people - Meyliyeva G.R. (Zien Journals, 2024)
The article discusses Geographical names for different locations. In the study of ethnic history and peoples' settlement, ethnotoponyms are crucial because they reveal the ethnic makeup of the populace
Keywords: toponyms; geographical names; tribes; clans